Markets for Technology: The Economics of Innovation and Corporate StrategyMarkets for Technology: The Economics of Innovation and Corporate Strategy, by AroraAshish FosfuriAndrea, and GambardellaAlfonso. Cambridge, MA: MIT Press, 2001. - Greenstein, Shane (Academy of Management Review, 2002)
The article reviews the book “Markets for Technology: The Economics of Innovation and Corporate Strategy,” by Ashish Arora, Andrea Fosfuri and Alfonso Gambardella.